The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1021/jo400386f
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Approach to Hyacinthacines B1 and B2

Abstract: Naturally occurring hyacinthacines B1 and B2 have been prepared from a common, easily available, advanced intermediate. The approach features several highly stereoselective transformations: inter alia, a dichloroketene-enol ether [2 + 2] cycloaddition, a Bruylants alkylation, and an amino-nitrile alkylation-reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 86 publications
1
11
0
Order By: Relevance
“…Nevertheless, the stereochemistry of the new C‐5 stereogenic center could not be established at this stage of synthesis due to the overlapping signals of the H‐3 and H‐5 protons (m, 3.39–3.45 ppm). As was evidenced later, the NMR spectra of the unnatural (–)‐enantiomer of hyacinthacine B 2 ( 2 ) synthesized by our group were in good agreement with those recorded for the natural sample, as well as for the synthetic (+)‐hyacinthacine B 2 . This data confirmed that the absolute configuration at the C‐5 atom in 7 must be R .…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Nevertheless, the stereochemistry of the new C‐5 stereogenic center could not be established at this stage of synthesis due to the overlapping signals of the H‐3 and H‐5 protons (m, 3.39–3.45 ppm). As was evidenced later, the NMR spectra of the unnatural (–)‐enantiomer of hyacinthacine B 2 ( 2 ) synthesized by our group were in good agreement with those recorded for the natural sample, as well as for the synthetic (+)‐hyacinthacine B 2 . This data confirmed that the absolute configuration at the C‐5 atom in 7 must be R .…”
Section: Resultssupporting
confidence: 85%
“…The optical rotation value for the obtained product (–)‐ 2 {[α] D 23 =–22.5 ( c 1.0, H 2 O)} resembled the absolute value of the optical rotation for the synthetic natural (+)‐hyacinthacine B 2 {[α] D 23 =+25.0 ( c 0.32, H 2 O)} to a greater extent than the natural sample {[α] D =+41.3 ( c 0.36, H 2 O)} and the synthetic product firstly prepared by Yoda and co‐workers {[α] D 27 =+42.3 ( c 0.25, H 2 O)} . Fortunately, the 1 H and 13 C NMR data of our compound (–)‐ 2 were in good agreement with those described for the natural sample and reported by Delair for the synthetic natural (+)‐hyacinthacine B 2 . Only minor differences in the chemical shifts were observed (see Supporting information, Tables 1 and 2), which can be attributed to a different chemical environment during the process of isolating and purifying the final pyrrolizidine (pH, variation in solvent, metal contaminants) ,…”
Section: Resultsmentioning
confidence: 90%
“…Hyacinthacines are also accessible through aminonitrile chemistry, which was demonstrated in 2013 by Delair and co‐workers, who reported the total synthesis of hyacinthacines B 1 and B 2 (Scheme ) . In view of their polyhydroxylated pyrrolizidine structure, they can be considered as imino sugars which are currently among the most extensively studied glycosidase inhibitors for drug development .…”
Section: α‐Aminonitriles As Key Intermediates In Natural Product Syntmentioning
confidence: 99%
“…9 In order to facilitate their synthesis, several diastereoselective approaches to these heterocyclic frameworks have been successfully attempted. For instance, chain elongations of proline derivatives followed by cyclization, 10 transanular iodoamination 11 using lactams, 12 from other natural products, 13 etc. However, the most important and straightforward route is to employ a 1,3-dipolar cycloaddition (1,3-DC) 14,15,16 using mainly nitrones 17,18,19,20 or azomethine ylides.…”
Section: Introductionmentioning
confidence: 99%